2018
DOI: 10.1161/hypertensionaha.118.11594
|View full text |Cite
|
Sign up to set email alerts
|

Office and Ambulatory Heart Rate as Predictors of Age-Related Kidney Function Decline

Abstract: The decline in glomerular filtration rate (GFR) associated with aging is one of the most important predisposing causes of kidney failure in old age. Identifying persons at risk for accelerated GFR decline is an essential first step in the development of preventive measures to preserve kidney function in the elderly. Heart rate (HR) has not yet been studied as a risk factor for GFR decline in the general population. In the RENIS-T6 (Renal Iohexol-Clearance Survey in Tromsø 6), we measured baseline ambulatory HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…There is no consensus on the definition of accelerated GFR decline in population-based studies, and some have used an absolute or percentage change in GFR based on the baseline to FU assessment [ 8 , 9 , 26 ]. This method provides an imprecise estimate of GFR change that is more prone to misclassification compared with using the rate of GFR change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on the definition of accelerated GFR decline in population-based studies, and some have used an absolute or percentage change in GFR based on the baseline to FU assessment [ 8 , 9 , 26 ]. This method provides an imprecise estimate of GFR change that is more prone to misclassification compared with using the rate of GFR change.…”
Section: Discussionmentioning
confidence: 99%
“…In sensitivity analyses, we defined accelerated GFR decline as the 25% fastest decliners based on the GFR slope calculated as described above, and as an annual GFR loss of >3 mL/min/1.73 m 2 or as twice the unadjusted cohort mean (calculated by the difference in GFR from baseline to FU divided by the observation time), methods that have been used in previous studies [ 8 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are data showing an association between baseline blood pressure (BP) and subsequent GFR decline and/or development of CKD. However, some authors shown no relationship between these factors [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate (HR) is a clinically accessible indicator of vital signs and sympathetic activity, 4 which has been reported to be predictive of all‐cause mortality, cardiovascular disease, and renal outcome. 5 , 6 , 7 Similar to blood pressure, HR follows circadian rhythms; that is, it normally decreases by 10–20% at night due to the effect of the parasympathetic system, 8 , 9 a night HR decline less than 10% from day is defined as the HR non‐dippers.…”
Section: Introductionmentioning
confidence: 99%